Cultura organizacional e ambiente propício ao desenvolvimento de inovações: um estudo em uma organização de serviços - Fernandes Neto, Manuel (2019)
Innovation is understood in this research as the result by which new practices, products, and services are developed. Such services, and practices can generate results that, when innovated, try to meet the demands of the market. This study, therefore, engages with recent studies that deal with the presence of an environment favorable to innovation, respecting and being guided by theoretical perspectives built by classical authors in this field of study, as Geert Hofstede and Edgar Schein. In addition, this study included the retail sector as object of analysis as a favorable environment for the development of innovations. To achieve the objective of analyzing the relationship between the cultural dimensions on the external and internal aspects of the innovation development in a retail supermarket chain, the research was conducted in one of the units of the selected retail chain, where a questionnaire, designed by Machado, Carvalho, and Heinzmann (2012), was distributed to all employees. From a total of 312 employees, 258 participants answered the questionnaire, and the data obtained was assessed by means of structural equation modeling (SEM) after tabulation in statistical analysis software – Microsoft Excel, SPPS, and Stata, respectively. As result of this research, it was possible to identify that the employees perceive the culture of the organization analyzed as having a high level of collectivism, high cultural congruency, and a small distance of power. The combination of such characteristics favors an environment that can be described as a favorable to the development of innovations. In this sense, the teamwork and the exchange between different sectors and employees are also perceived as something positive and present, as part of the process of development of innovation in the company analyzed. In conclusion, it is possible to affirm that the cultural organization exerts influence over the favorable environment for the development of innovations in the company analyzed.